Politeness Strategies Of Request Utterances In Romantic Movie Script - Rachmasari, Tri Agustin; , Agus Wijayanto, Ph.D; , Dra. Siti Zuhriyah Ariatmi, M. Hum (2013)
The aims of this research are to describe the types of request used in romantic movie script, to describe the pramalinguistic forms of request used in romantic movie script and to determine types of politeness strategy used in request in romantic movie script. The type of this research is descriptive qualitative research. The researcher uses romantic movie script, they are Dear John, The Vow, and Letter to Juliet as the data source. The researcher employs documentation and observation as the method of collecting data with the techniques: watching, reading and identifying, classifying, coding, and categorizing the data. In analyzing the data, the writer describes the type of request strategy, describes pragmalinguistics form of request using Trosborg theory (1995) and describes politeness strategies using Brown and Levinson's theory (1987). The result of this research shows that there are many types of request strategies from sixty three data (100%) found in this movie. They are Hints (7,94%), Ability Willingness and Permission (38,10%), Suggestory Formulae (1,59%), Wishes (3,17%), Desires/Needs (6,35%), Obligation and Necessity ( 1,59%) and Imperative (41,27%). The writer did not find the request type in performative. The pragmalinguistic form of strategies include Syntactic Downgrades, Lexical/Phrasal Downgrades, Supportive Reasons. Politeness strategies are Bald On Record, Positive Politeness, Negative Politeness, Off Record.